A method for preparing porous nano zinc oxide material

Porous nano zinc oxide materials were prepared by light-induced polarization, which solved the problem of low utilization efficiency of zinc oxide photoelectrodes on sunlight, and achieved the effect of improving the kinetics of water oxidation reaction and carrier recombination rate.

CN115928094BActive Publication Date: 2025-02-07GUANGZHOU HENGHUI HYDROGEN ENERGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211160655.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-22
Publication Date
2025-02-07
Estimated Expiration
2042-09-22

AI Technical Summary

Technical Problem

In the prior art, due to the wide band gap, zinc oxide (ZnO) photoelectrodes can only use ultraviolet light to excite photogenerated electrons and holes, resulting in low utilization efficiency of sunlight, slow kinetics of water oxidation reaction, and carriers. High compounding rate.

Method used

Porous nanozinc oxide materials were prepared by light-induced-polarization method. By placing the nanomaterial photoanode in the electrolyte, applying voltage and light, the photocorrosion process of the surface interface was controlled to construct a multi-porous microstructure.

Benefits of technology

The porosity and specific surface area of ​​porous nano zinc oxide materials are improved, the active reaction sites of the photocatalyst are enhanced, the surface charge separation efficiency is improved, and the carrier recombination rate is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure HDA0003859763360000011
    Figure HDA0003859763360000011
  • Figure HDA0003859763360000012
    Figure HDA0003859763360000012
Patent Text Reader

Abstract

The present application discloses a method for preparing a porous nano zinc oxide material. The specific preparation method is as follows: using FTO as a conductive substrate, growing nano zinc oxide material on the surface of FTO, and preparing the porous nano zinc oxide material using light-induced polarization technology. By testing the photoelectrochemical performance thereof, it is found that the porous nano zinc oxide material has significantly enhanced photoelectric properties. The technical process of the present application is very simple, easy to realize industrial production, and the reagents are cheap. The porous nano zinc oxide material obtained by this method has excellent photoelectric properties and can be applied to information storage and display, preparation of solar photovoltaic cells, construction of photoelectrochemical sensors, photoelectrocatalytic water decomposition to produce hydrogen, photoelectrocatalytic degradation of organic pollutants, medicine, biology and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing a porous nano zinc oxide material, belonging to the technical field of nano materials. Background Art

[0002] Photoelectrochemical water splitting uses clean, renewable solar energy to decompose water to produce hydrogen. The reaction process does not cause environmental pollution, and the use of hydrogen does not damage the environment (hydrogen burns to produce water). Therefore, photoelectrochemical water splitting technology has attracted widespread attention from scientific researchers in terms of green energy renewable utilization. When the energy of the incident light is greater than the semiconductor band gap energy, the electrons on the valence band (VB) are excited to jump to the conduction band (CB), reducing water to hydrogen, leaving corresponding photogenerated holes in the VB, oxidizing water to oxygen. It is a low-cost, environmentally friendly hydrogen production technology. Zinc oxide (ZnO) is a semiconductor material that is cheap, easy to prepare, and has a high electron mobility (205-1000 cm 2 V -1 s -1 ) is one of the most studied photoanodes. However, due to the wide band gap of ZnO (3.2eV), it can only be excited by ultraviolet light to produce photogenerated electrons and holes, resulting in low efficiency in the use of sunlight, resulting in slow water oxidation reaction kinetics and high carrier recombination rate. The construction of micromorphology is the most common means to change the specific surface area, light collection and photogenerated carrier transmission distance of PEC water splitting photoelectrodes. Studies have shown that hollow or porous micromorphology has stronger light scattering, and the shorter carrier transmission distance can promote bulk charge separation and inhibit the recombination of photogenerated carriers in the bulk phase. In particular, photoelectrodes with porous structures or nanostructures have relatively short charge transmission distances compared to bulk electrodes. At the same time, the increase in specific surface area will increase the surface reaction sites accordingly, which helps to reduce the recombination of carriers. However, at present, ZnO nanotubes are all made by etching with sodium hydroxide, and the etching process is not easy to control, resulting in large pores and small specific surface area. Therefore, a new mild and controllable method is developed to prepare porous nano zinc oxide materials to improve the kinetics of water oxidation reaction and the high recombination rate of photogenerated carriers. There has been no report on the preparation of porous nano zinc oxide materials by light-induced-electrochemical polarization technology and their application in photoelectrochemical water decomposition to produce hydrogen. Summary of the invention

[0003] According to one aspect of the present application, a method for preparing a porous nanomaterial is provided.

[0004] A method for preparing a porous nanomaterial, wherein the preparation method is a light-induced polarization method.

[0005] The light-induced polarization method comprises the following steps:

[0006] (1) obtaining a nanomaterial photoanode;

[0007] (2) placing the nanomaterial photoanode obtained in step (1) in an electrolyte, applying voltage and light, reacting, and obtaining the porous nanomaterial.

[0008] Optionally, the nanomaterial includes zinc oxide nanoparticles, zinc oxide nanorods, zinc oxide nanosheets, and zinc oxide nanowires.

[0009] Optionally, the electrolyte in step (2) has a composition and a molar ratio of:

[0010] Component A 0.5-1.5mol / L

[0011] Component B 0.5-1.5mol / L.

[0012] The component A includes at least one of boric acid, sulfurous acid and phosphoric acid.

[0013] The component B includes at least one of potassium hydroxide and sodium hydroxide.

[0014] The core of pore construction is to convert surface photocorrosion into pitting corrosion. Pitting corrosion occurs above a specific critical potential and active anions. Reducing anions can serve as active anions.

[0015] Optionally, the illumination in step (2) is performed under the following conditions:

[0016] The intensity of the light is 20-300W / cm 2 ;

[0017] The wavelength range of the illumination is full light (nm);

[0018] The illumination time is 0-25h;

[0019] Optionally, the voltage in step (2) is 1.0-2.0V. RHE .

[0020] The porous nano zinc oxide material is caused by the accumulation of photogenerated holes in zinc oxide on the surface of the photoanode. The reaction equation for the generation of holes is ZnO+2h + →Zn 2+ +1 / 2O2. When the semiconductor is irradiated with light with energy higher than the bandgap width, the electrons in the semiconductor are excited to jump from the valence band to the conduction band. This promotes the generation of photogenerated electrons-holes, and then increases the generation of pores. When the energy of the bias voltage is not higher than the bandgap width, porous materials cannot be produced. When the energy of the bias voltage is too high, the pores of the porous material produced are too large, destroying the pore structure.

[0021] Optionally, when the target product is nanorods, nanoparticles and nanowires, the method of step (1) comprises the following steps:

[0022] (1) coating the reaction solution I on a substrate, performing reaction I, and obtaining a substrate on which a nanocrystal seed film is immobilized;

[0023] (2) placing the substrate on which the nanocrystal seed film is immobilized in reaction solution II, and performing reaction II to obtain a substrate;

[0024] (3) The substrate obtained in step (2) is subjected to reaction III to obtain the nanomaterial photoanode.

[0025] Optionally, the coating method in step (1) includes at least one of spin coating, dip coating, and ion sputtering;

[0026] Optionally, in the reaction I, the reaction temperature is 300-400° C. and the reaction time is 10-30 min.

[0027] Optionally, the reaction solution I comprises a solvent and a salt, the solvent is selected from at least one of ethanol, water and methanol; the salt is composed of cations of nanomaterials and acetic acid anions; and the concentration of the salt in the solvent is 0.002-0.02 mol / L.

[0028] Optionally, in the reaction II in step (2), the reaction temperature is 80-100° C. and the reaction time is 8-15 h.

[0029] Optionally, the solvent of the reaction solution II is water, and the solute includes a salt composed of nanomaterial metal cations and nitrate anions, and hexamethylenetetramine; preferably, the concentration of the salt is 0.05-1 mol / L, and the concentration of the hexamethylenetetramine is 0.05-1 mol / L.

[0030] Optionally, in the reaction III in step (3), the reaction temperature is 300-400° C. and the reaction time is 30-90 min.

[0031] Optionally, when the target product is a nanosheet, the method in step (1) comprises the following steps:

[0032] (1) placing the substrate on which the film is fixed in the reaction solution I, performing reaction IV, and obtaining nanosheets;

[0033] Preferably, the reaction solution I comprises a solvent and a salt, wherein the solvent is selected from at least one of ethanol, water and methanol; the salt is composed of cations of the nanomaterial and acetic acid anions; and the concentration of the salt in the solvent is 0.002-0.02 mol / L.

[0034] Preferably, the reaction IV comprises the following steps: applying a voltage of -1.1 to -1.5 V for a reaction of 8 to 15 seconds; then adjusting the voltage to -0.9 to -1.1 V and reacting for 300 to 500 seconds.

[0035] The porous microstructure of zinc oxide photoanode was constructed by using different types of reducing ions (BO3 3- , SO3 2- , I - ) aqueous solution as the electrolyte, the photoanode was polarized under different constant voltage treatments and simulated sunlight illumination using the chronoamperometry method. The porous microstructure is obtained by controlling the surface interface photocorrosion process. The reaction that occurs is ZnO+2h + =Zn 2+ +1 / 2O2.

[0036] The beneficial effects of this application include:

[0037] 1) The porous nano zinc oxide material provided in the present application has a high porosity and a specific surface area of ​​1.3 times. When used as a photocatalyst, it can provide more active reaction sites and improve the surface charge separation efficiency by 30%.

[0038] 2) The method for preparing the porous nano zinc oxide material provided in the present application is simple in preparation and can effectively control the pore size, thus having very good industrial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a transmission electron microscope image of the porous nano zinc oxide material obtained in Example 1 of the present application.

[0040] Figure 2 This is the X-ray powder diffraction pattern of the porous nano zinc oxide material obtained in Example 1 of the present application.

[0041] Figure 3 These are the light response curves of the porous nano zinc oxide material and the zinc oxide nano material obtained in Example 1 of the present application.

[0042] Figure 4 This is a transmission electron microscope image of the porous nano zinc oxide material obtained in Example 2 of the present application. DETAILED DESCRIPTION

[0043] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0044] Unless otherwise specified, the raw materials and catalysts in the examples of this application were purchased through commercial channels.

[0045] The analysis method in the examples of this application is as follows:

[0046] X-ray powder diffraction, scanning electron microscopy and transmission electron microscopy were used to analyze the microscopic morphology and structure, and an electrochemical workstation was used to test the photoelectrochemical properties of porous nano zinc oxide materials.

[0047] Among them, the model of X-ray powder diffraction equipment is: Bruker D8 DISCOVER

[0048] The model of the scanning electron microscope equipment is: TESCAN MIRA3 LMU

[0049] The model of the transmission electron microscope equipment is: JEM-2100

[0050] The model of the electrochemical workstation is: Chenhua 760D

[0051] Example 1

[0052] Add zinc acetate dihydrate to 50 ml of ethanol and continue stirring until dissolved. Spin-coat the prepared solution onto FTO conductive glass (1×2 cm 2 ), and then the prepared sample was placed in a tube furnace and annealed at 350°C for 20 minutes in an air atmosphere to obtain a zinc oxide seed layer sample. The prepared seed layer sample was placed vertically in the inner liner of an autoclave, and then an aqueous solution of 0.06M hexamethylenetetramine and 0.06M zinc nitrate was slowly poured into the inner liner of the reactor and kept at 95°C for 10 hours. The sample material was then annealed at 400°C for 60 minutes in an air atmosphere to obtain zinc oxide nanorods. The prepared zinc oxide nanorods were placed in a 1 mol / L potassium borate solution and heated at 1.6V RHE The porous nano zinc oxide material was successfully prepared by irradiating light under bias for up to 10 hours.

[0053] Example 2

[0054] Add zinc acetate dihydrate to 50 ml of ethanol and continue stirring until dissolved. Spin-coat the prepared solution onto FTO conductive glass (1×2 cm 2 ), and then put the prepared sample into a tube furnace and annealed at 350°C for 20 minutes in an air atmosphere to obtain a zinc oxide seed layer sample. The prepared seed layer sample was placed vertically in the inner liner of an autoclave, and then an aqueous solution of 0.06M hexamethylenetetramine and 0.06M zinc nitrate was slowly poured into the inner liner of the reactor and kept at 95°C for 10 hours. The sample material was then annealed at 400°C for 60 minutes in an air atmosphere to obtain zinc oxide nanorods. The prepared zinc oxide nanorods were placed in a 0.5mol / L sodium sulfite solution and heated at 1.6V RHEThe porous nano zinc oxide material was successfully prepared by irradiating light under bias for up to 10 hours.

[0055] Example 3

[0056] Add zinc acetate dihydrate to 50 ml of ethanol and continue stirring until dissolved. Spin-coat the prepared solution onto FTO conductive glass (1×2 cm 2 ) on, and then put the prepared sample into a tube furnace and anneal at 350°C for 20 minutes in an air atmosphere to obtain a zinc oxide seed layer sample. The prepared seed layer sample was placed vertically in the inner liner of an autoclave, and then an aqueous solution of 0.06M hexamethylenetetramine and 0.06M zinc nitrate was slowly poured into the inner liner of the reactor and kept at 95°C for 10 hours. The sample material was then annealed at 400°C for 60 minutes in an air atmosphere to obtain zinc oxide nanorods. The prepared zinc oxide nanorods were placed in a 1 mol / L potassium phosphate solution and heated at 1.2V. RHE The porous nano zinc oxide material was successfully prepared by irradiating light under bias for up to 10 hours.

[0057] Example 4

[0058] Add zinc acetate dihydrate to 50 ml of ethanol and continue stirring until dissolved. Spin-coat the prepared solution onto FTO conductive glass (1×2 cm 2 ) on, and then put the prepared sample into a tube furnace and anneal at 350°C for 20 minutes in an air atmosphere to obtain a zinc oxide seed layer sample. The prepared seed layer sample was placed vertically in the inner liner of an autoclave, and then an aqueous solution of 0.06M hexamethylenetetramine and 0.06M zinc nitrate was slowly poured into the inner liner of the reactor and kept at 95°C for 10 hours. The sample material was then annealed at 400°C for 60 minutes in an air atmosphere to obtain zinc oxide nanorods. The prepared zinc oxide nanorods were placed in a 1 mol / L potassium phosphate solution and heated at 1.6V RHE The porous nano zinc oxide material was successfully prepared by irradiating light under bias for up to 10 hours.

[0059] Example 5

[0060] Nanosheet zinc oxide was prepared by electrodeposition. The electrodeposition was carried out in an electrochemical cell, and 0.14 M zinc acetate and 0.14 M zinc nitrate were added to 100 ml of aqueous solution as the electrolyte solution, and the temperature was maintained at 85°C. FTO was used as the working electrode, and the platinum sheet and silver / silver chloride electrode were used as the counter electrode and reference electrode, respectively. First, a thin layer of zinc oxide seeds was obtained by applying a -1.3 V (VS. silver / silver chloride) bias treatment on FTO for 10 seconds. Then a -1.0 V potential (VS. silver / silver chloride) bias treatment was applied for 400 seconds. The nanosheet zinc oxide obtained on FTO was washed, dried, and then calcined at 350°C for 1 hour in an argon atmosphere. The prepared zinc oxide nanosheets were placed in a 1 mol / L potassium borate solution and heated to 1.6 V. RHE The porous nano zinc oxide material was successfully prepared by irradiating light under bias for up to 10 hours.

[0061] Example 6

[0062] Nanosheet zinc oxide was prepared by electrodeposition. The electrodeposition was carried out in an electrochemical cell. 0.14 M zinc acetate and 0.14 M zinc nitrate were added to 100 ml of aqueous solution as the electrolyte solution, and the temperature was maintained at 85°C. FTO was used as the working electrode, platinum sheet and silver / silver chloride electrode as the counter electrode and reference electrode, respectively. First, a thin layer of zinc oxide seeds was obtained by applying a -1.3 V (VS. silver / silver chloride) bias treatment on FTO for 10 seconds. Then a -1.0 V potential (VS. silver / silver chloride) bias treatment was applied for 400 seconds. The nanosheet zinc oxide obtained on FTO was washed, dried, and then calcined at 350°C for 1 hour in an argon atmosphere. The prepared zinc oxide nanosheets were placed in a 1 mol / L potassium phosphate solution and heated at 1.2 V. RHE The porous nano zinc oxide material was successfully prepared by irradiating light under bias for up to 10 hours.

[0063] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a porous nanomaterial, characterized in that: The preparation method is a light-induced polarization method; the light-induced polarization method comprises the following steps: (1) Obtaining nanomaterial photoanode; (2) placing the nanomaterial photoanode obtained in step (1) in an electrolyte, applying voltage and light, reacting, and obtaining the porous nanomaterial; The intensity of the light is 20-150 W / cm 2 ; The illumination time is 10-25 h; The voltage condition is 1.0-2.0 V RHE ; The nano material is any one of zinc oxide nanoparticles, zinc oxide nanorods, zinc oxide nanosheets and zinc oxide nanowires.

2. The preparation method according to claim 1, characterized in that: The electrolyte in step (2) has a composition and a molar ratio of: ; The component A includes at least one of boric acid, sulfurous acid and phosphoric acid; The component B includes at least one of potassium hydroxide and sodium hydroxide.

3. The preparation method according to claim 1, characterized in that: The illumination in step (2) has a wavelength range of full light.

4. The preparation method according to claim 1, characterized in that: When the target product is nanorods, nanoparticles and nanowires, the method of step (1) comprises the following steps: (1) coating a reaction solution I on a substrate, wherein the reaction solution I comprises a solvent and a salt, wherein the solvent is selected from at least one of ethanol, water, and methanol, and the salt is composed of cations of nanomaterials and acetic acid anions, and the concentration of the salt in the solvent is 0.002-0.02 mol / L, and performing a reaction I at a temperature of 300-400° C. and a time of 10-30 min to obtain a substrate on which a nanocrystalline seed film is immobilized; (2) placing the substrate on which the nanocrystalline seed film is immobilized in reaction solution II, wherein the solvent of the reaction solution II is water, and the solute includes a salt composed of a metal cation of the nanomaterial and a nitrate anion, and hexamethylenetetramine, wherein the concentration of the salt is 0.05-1 mol / L, the concentration of the hexamethylenetetramine is 0.05-1 mol / L, and the reaction II is carried out at a temperature of 80-100 °C and a reaction time of 8-15 h to obtain a substrate; (3) The substrate obtained in step (2) is subjected to reaction III, wherein the temperature of reaction III is 300-400° C. and the reaction time is 30-90 min to obtain the nanomaterial photoanode.

5. The preparation method according to claim 4, characterized in that: The coating includes at least one of spin coating, dip coating and ion sputtering.

6. The preparation method according to claim 2, characterized in that: When the target product is a nanosheet, the method of step (1) comprises the following steps: The substrate on which the film is fixed is placed in the reaction solution I, and the reaction is IV to obtain the nanosheet; The reaction solution I comprises a solvent and a salt, wherein the solvent is selected from at least one of ethanol, water and methanol; the salt is composed of cations of nanomaterials and acetic acid anions; and the concentration of the salt in the solvent is 0.002-0.02 mol / L; The reaction IV comprises the following steps: applying a voltage of -1.1 to -1.5 V for a reaction of 8 to 15 seconds; then adjusting the voltage to -0.9 to -1.1 V for a reaction of 300 to 500 seconds.

Citation Information

Patent Citations

  • Nanometer oxide porous membrane electrode and preparing method and application thereof

    CN101232049A

  • Anode electrode for visible light decomposition of water, method for producing the same, and apparatus for visible light decomposition of water

    JP2012197469A